The Subject, Object and the Duty to Provide Evidence - Murzea, Cristinel Ioan (Bulletin of the Transilvania University of Brașov. Series VII, Social sciences, law, 2020)
In our usual language, the word “evidence” represents themental and logical operation by which we attempt to prove something, todemonstrate, to emphasize a statement which provides credibility to acertain situation. The institution of evidence in the system of objective lawwas regulated in certain legal texts, with different regulations, from materiallaw to procedural law, depending on the different factors which configureprivate law, but also in direct connection with the lawmaker’s interest. As aconsequence, in the past, the matter of evidence was studied within thegeneral theory of civil law, whereas, in present times, evidence is studiedwithin Civil Procedural Law. The matter of evidence would be knowndifferently and treated differently both by law and by doctrine, thus having adifferent space “and a different setting between the institutions of civilmaterial and procedural law”.